Optimal planning of artificial lift operations in a shale gas multiwell pad. Issue 4 (19th January 2021) - Achkar, Victoria G.; Cafaro, Vanina G.; Méndez, Carlos A.; Cafaro, Diego C.
Abstract: Lifting operations play a key role to sustain shale gas wells productivity. Artificial Lift Systems (ALS) involve a wide range of techniques aimed at deliquifying wells. Although these operations are relatively mature for vertical wells in conventional reservoirs, enhancing productivity from shale gas wells has become a new frontier for unconventional production. The main contribution of this work is the development of the first Mixed Integer Linear Programming (MILP) formulation determining the integrated planning of several ALS in a multiwell pad. The model simultaneously manages ALS selection, investment and operational decisions, hedging against rapid decline curves in different wells. We introduce very detailed piecewise functions accounting for the ALS installation and removal times. The performance of the MILP is evaluated by solving five illustrative case studies.